Computational design and synthesis of molecular imprinted membranes for selective extraction of quercetin / Siti Fatimah Kamarudin. - Siti Fatimah Kamarudin (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
This research aims to develop quercetin imprinted membrane (QIM) which have higher binding capacity and selectivity towards quercetin. This objective is accomplished through the following specific objectives ; to determine the most favourable functional monomer and optimum molar ratio of pre-polymerization complexes between template-monomer using computational -aided tool (HyperChem) ; to synthesize quercetin imprinted membrane (QIM) and non-imprinted membrane (NIM) using surface imprinting polymerization methodand characterize them using FTIR, AFM and FESEM analysis ; to analyse the performance of QIM and NIM for extraction of quercetin through batch and kinetic binding as well as selectivity studies.